Technology transfer : rejuvenating matured industries - Moonan, Shastri, 1946- (Garland studies on industrial productivity., 2012)
This study focuses on technology transfer in the steel mini-mill industry. It identifies two central issues: how capacity is built and how demand is sustained, developing a three-dimensional perspective to bring into sharp focus the desirability and necessity of technology transfer. The three-dimensional perspective focuses on the changes in the marketplace for flat steel sheets, the responsiveness and sensitivity to these market changes, and applying the best available technology to obtain a high quality product. Prior to this study, technology transfer has been examined in a bivariate relati.